The identification of critical occupational risks and the determination of priority preventive measures in the rotary kiln area of cement - Aouad, Razika; Belhour, Samira; Chaib, Rachid; Nettour, Djamel (Technology audit and production reserves, 2026)
The objects of this research are occupational risks and priority preventive measures in the zone of the rotary kiln used in cement production. The identification of these objects is essential for housing development and infrastructure, but cement production is involving serious professional risks. Consequently, an evaluation of these is necessary; it is a critical stage in prevention process, aiming to prioritize actions in order to implement preventive measures. Therefore, an evaluation was triggered following a noticeable increase of five (05) accidents compared with 2021, with 16 accidents in 2022, to which workers in the rotary kiln zone were exposed. The adopted methodology, namely risk mapping, constitutes a strategic management tool that enables the identification, assessment, prioritization, and visualization of potential threats affecting the study area. Widely applied in industrial contexts, it offers a comprehensive representation and a systematic inventory of existing and potential hazards in both temporal and spatial dimensions. This facilitates risk management in a more informed and effective way. Furthermore, this offers decision-makers a clear overview to develop proactive action plans and allows them to monitor the effectiveness of implemented strategies. To obtain good results, qualitative and quantitative methods were applied, including the Ishikawa diagram, FMEA, and root cause analysis. These tools enabled the identification of the root causes of accidents in the studied zone. The survey results prove that gas leaks constitute the most critical hazards because of their potential to initiate fires. The findings offer a clear and comprehensive overview of occupational hazard distribution in the study zone, supporting the development of a planned prevention strategy to safeguard workers’ health, enhance operational safety, and foster a sustainable safety culture.